Neonatal periventricular leukomalacia: current perspectives - Ahya KP; Suryawanshi P (Dove Medical Press, 2018)
Kunal P Ahya,1 Pradeep Suryawanshi2 1Department of Neonatology, Maahi Newborn Care Centre, Rajkot, Gujarat, 2Department of Neonatology, BVDU Medical College, Pune, Maharashtra, India Abstract: Significant advances in the neonatal ICU have improved the survival of extreme premature neonates; with this comes the importance of intact survival. Periventricular leukomalacia (PVL) is the commonest white matter brain injury in preterm infants. It has a typical distribution at the watershed areas adjacent to the lateral ventricles. PVL occurs because of ischemic injury to periventricular oligodendrocytes of the developing brain. It can be detected by cranial ultrasonography (CUS) as initial periventricular echodensities, followed later by cystic formation. Recent magnetic resonance imaging studies have shown that it helps in early visualization of PVL and also detection of non-cystic form of PVL, which is not picked up by CUS. It is the commonest cause of cerebral palsy, intellectual impairment or visual disturbances. Currently, no medical treatment is available for PVL; prevention and close developmental follow-up are the only options. Keywords: periventricular leukomalacia, preterm brain injury, cranial ultrasonography